Enhancement of Generator Contribution Allocation Using Power Tracing Approaches in Deregulated Power Systems - Syarifuddin Nojeng; Muhammad Nawir; Reny Murniati; Hariani Ma’tang Pakka; Amelya Indah Pratiwi (International Journal Of Electrical Engineering and Inteligent Computing, 2025)
The implementation of transmission open access in deregulated power systems requires transparent and equitable allocation of transmission usage among market participants. A key challenge is determining the actual contribution of individual generators to transmission line flows, particularly in meshed networks where loop flows and counterflows occur. Although power tracing based allocation methods are widely adopted due to their conceptual simplicity, classical approaches often fail to accurately represent generator responsibility under such conditions. This paper presents a comparative evaluation of generator contribution allocation using three representative power tracing approaches: the Bialek proportional sharing method, the Extended Incidence Matrix (EIM) approach, and the Generalized Generation Distribution Factor (GGDF) based method. A unified DC power flow–based analytical framework is employed to ensure consistent assessment in a deregulated transmission environment. A standardized 6-bus test system is used to illustrate the differences among the examined approaches. The results show that proportional tracing methods allocate only positive contributions, whereas the GGDF-based formulation is able to capture counterflow effects through negative contribution values. The findings provide useful insights for transmission usage allocation and congestion-related applications in deregulated electricity markets.